Extensor carpi ulnaris muscle shows unexpected slow-to-fast fiber-type switch in Duchenne muscular dystrophy dogs - Chady H. Hakim; Hsiao T. Yang; Matthew J. Burke; James Teixeira; Gregory J. Jenkins; N. Nora Yang; Gang Yao; Dongsheng Duan (The Company of Biologists, 2021)
Aged dystrophin-null canines are excellent models for studying experimental therapies for Duchenne muscular dystrophy, a lethal muscle disease caused by dystrophin deficiency. To establish the baseline, we studied the extensor carpi ulnaris (ECU) muscle in 15 terminal age (3-year-old) male affected dogs and 15 age/sex-matched normal dogs. Affected dogs showed histological and anatomical hallmarks of dystrophy, including muscle inflammation and fibrosis, myofiber size variation and centralized myonuclei, as well as a significant reduction of muscle weight, muscle-to-body weight ratio and muscle cross-sectional area. To rigorously characterize the contractile properties of the ECU muscle, we developed a novel in situ assay. Twitch and tetanic force, contraction and relaxation rate, and resistance to eccentric contraction-induced force loss were significantly decreased in affected dogs. Intriguingly, the time-to-peak tension and half-relaxation time were significantly shortened in affected dogs. Contractile kinetics predicted an unforeseen slow-to-fast myofiber-type switch, which we confirmed at the protein and transcript level. Our study establishes a foundation for studying long-term and late-stage therapeutic interventions in dystrophic canines. The unexpected myofiber-type switch highlights the complexity of muscle remodeling in dystrophic large mammals. This article has an associated First Person interview with the first author of the paper.